The -Hausdorff, -regular and -normal ideal spaces (2020)
We introduce and study new extensions of some separation axioms to ideal topological spaces, which we have called -Hausdorff, -regular and -normal. These extensions are quite natural and represent a good improvement with respect to other extensions that have recently occurred, in which a level of separation that can be considered acceptable is not perceived.